2015
DOI: 10.1371/journal.pone.0121492
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Dihydrofolate Reductase Inhibitors Identified Using Chemogenomic Methods and In Vitro Validation

Abstract: The lack of success in target-based screening approaches to the discovery of antibacterial agents has led to reemergence of phenotypic screening as a successful approach of identifying bioactive, antibacterial compounds. A challenge though with this route is then to identify the molecular target(s) and mechanism of action of the hits. This target identification, or deorphanization step, is often essential in further optimization and validation studies. Direct experimental identification of the molecular target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…One point should be visited, NB in Pipeline Pilot was considerable slower than the NB trained in scikit-learn (20 minutes in scikit-learn compared with 31 hours, Supplementary table 3 ). This is caused by the calculation of the background scores (see methods for details) as was done previously [28]. Calculation of z-scores requires the prediction of all ligand – protein interactions in the matrix and is a lengthy procedure regardless of the high speed of NB.…”
Section: Resultsmentioning
confidence: 99%
“…One point should be visited, NB in Pipeline Pilot was considerable slower than the NB trained in scikit-learn (20 minutes in scikit-learn compared with 31 hours, Supplementary table 3 ). This is caused by the calculation of the background scores (see methods for details) as was done previously [28]. Calculation of z-scores requires the prediction of all ligand – protein interactions in the matrix and is a lengthy procedure regardless of the high speed of NB.…”
Section: Resultsmentioning
confidence: 99%
“…Again we found that there was a disparity in computational model generation, utilization and sharing and little effort in bringing many different approaches together [65] such as combining machine learning with docking [66]. Recently, chemogenomic methods and experimental validation were used to identify two compounds as dihydrofolate reductase (DHFR) inhibitors [67]. Validating such computational approaches experimentally is essential, whether that is similarity searching, pharmacophores [68] or machine learning [69].…”
Section: Machine Learning Models For M Tuberculosismentioning
confidence: 99%
“…Based on the chemical structure of the compounds, we can predict their interaction partners (protein targets) in an organism. This is done by comparing the structure of the compound to large curated literature-based databases of known compound-protein interactions such as DrugBank, ChEMBL, the Human Metabolome Database, and the Therapeutic Target Database [20][21][22][23]. In this chapter, we use the data in the ChEMBL database release 17 containing approximately 12 million data points [24,25].…”
Section: Protein Target Analysismentioning
confidence: 99%